Integrating Islamic Information Literacy Curriculum as an Institutional Strategy to Counter Digital Radicalism in Islamic Higher Education - Machsun Rifauddin; Nurdin Laugu; Sri Rohyati Zulaikha (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2026)
The transition of the literacy landscape from print sources to digital platforms creates new vulnerabilities in Islamic higher education, where uncurated internet access increases students' exposure to digital radicalism. This study aims to examine these vulnerabilities and formulate the integration of the Islamic information literacy curriculum as an institutional strategy to counter digital radicalism in State Islamic Higher Education Institutions (PTKIN). Using a qualitative multiple-case study design at UIN Sunan Kalijaga and UIN SATU Tulungagung, this study draws on in-depth interviews, observations, and document analysis as its main data sources. The findings show that students increasingly depend on algorithm-driven platforms to access Islamic literature. Without critical reasoning and adequate source verification, this dependence encourages identity-based validation and draws students into dogmatic echo chambers. Current academic library interventions still focus mainly on technical procedures, such as user education and database access, and do not yet address the critical evaluation of ideological content. In response to this gap, this study proposes an Islamic information literacy curriculum integration model as a systemic institutional strategy. The model transforms information literacy from a technical search skill into an academic curriculum component that strengthens critical reasoning, religious moderation, and digital resilience. Three pillars support its implementation: the codification of Islamic information literacy standards that fit Islamic scholarship, pedagogical collaboration between lecturers and librarians in designing research-based assignments, and continuous curriculum evaluation to maintain instructional quality and sustainability. This study contributes to Islamic higher education management by positioning curriculum integration as a preventive strategy against digital radicalism.